41.2k views
4 votes
5(y + 2) = 6(y - 1)
Show work
Please and thank you

User Damonsson
by
5.4k points

1 Answer

3 votes

Answer:

5 ( y + 2) = 6 ( y - 1)

- distribute the number outside into the parenthesis by multiplying it with each value

5y + 10 = 6y - 6

- subtract like terms, in this case 5y and 6y

-y + 10 = -6

- isolate the variable ( y) by getting rid of 10 by subtracting it to both sides

-y = -16

-1y = -16

- isolate variable (y) by getting rid of the -1 next to it by dividing it to both sides

y = -16 / -1

y = 16

User Ticallian
by
5.4k points